ANALISIS KANDUNGAN PEMANIS BUATAN PADA SARI BUAH MARKISA PRODUKSI MAKASSAR - Tahir, Ika Amilah Citra; Vitrianty, Vitrianty (Jurnal Ilmiah As-Syifaa, 2013)
An investigation on analyse of artificial sweeteners saccharin and cyclamate content has been done in Markisa essence beverage production in Makassar. The aim was to determinet the quantity of the sweeteners contained in the beverages. Four branded of the beverages that has been taken from several Supermakets in Makassra as the sample’s. quantitative analyse has done by spesific reagent mean while quantitative analyse by means of UV-Visible Spectrofotometry upon saccharin and Gravimetry method upon cyclamate. Result on quantitative test shown that these four sample’s containing these two artificial sweetenes. Quantitative test upon these four samples the concentration of saccharin was mero than the concetration that estabilished bt the departement of health and for cyclamate was met the requirement by the departement.Key words : Saccharin, Cyclamate, Markisa Essence Beverages Production, Makassar.